2018
DOI: 10.1108/jpcc-12-2017-0031
|View full text |Cite
|
Sign up to set email alerts
|

Student teachers’ emotions when watching their own videos and those of their peers

Abstract: Purpose The purpose of this paper is to explore the emotions reported by a group of student teachers (STs) after viewing their own teaching videos and those of their peers, as well as the reasons for those emotions. It also investigated the perceived influence of the STs’ emotions on their learning from the videos. Design/methodology/approach The case study involved 12 STs, and was situated in the context of a science methods course on a postgraduate teaching diploma program. The emotions associated with wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Furthermore, both constructs showed an overlap when predicting final exam scores in an introductory biology course at the university with almost the same magnitude. These findings support our assumption that emotional cost could be related to video-based learning during a teaching practicum, as previous research has pointed out anxiety as one of the most prevalent achievement emotions when using videos of one’s teaching (e.g., Chan et al, 2018 ).…”
Section: Introductionsupporting
confidence: 90%
See 3 more Smart Citations
“…Furthermore, both constructs showed an overlap when predicting final exam scores in an introductory biology course at the university with almost the same magnitude. These findings support our assumption that emotional cost could be related to video-based learning during a teaching practicum, as previous research has pointed out anxiety as one of the most prevalent achievement emotions when using videos of one’s teaching (e.g., Chan et al, 2018 ).…”
Section: Introductionsupporting
confidence: 90%
“…Counterintuitively, they found that participants in the "other video group" showed significantly more emotional expressions and a tendency toward more negative emotions. This finding is in stark contrast with Chan et al (2018). They found that student teachers experienced more frequent negative emotions such as anxiety or shame when watching videos of their own teaching compared to fewer negative and more positive emotions when watching videos of their peers.…”
Section: The Concepts Of Resonance and Immersionmentioning
confidence: 74%
See 2 more Smart Citations
“…Analysis of videoed simulations during simulated process is one of the most effective tools for mentoring in organizations. Analysis provides varied learning opportunities and in addition enables colleagues to learn about their skills and those of others (Chan et al., 2017). Mentoring through analysis of videos describing interactions occurring in the organization, helps mentees to sharpen their world-view and professional vision, leading to testing strategies for solution (Hollingsworth & Clarke, 2017).…”
Section: Introductionmentioning
confidence: 99%